DYNAMIC OF INDOLE ALKALOIDS IN A SOIL AND ITS RELATIONSHIPS WITH ALLELOPATHIC PROPERTIES - Sylvia Violeta Copaja (Journal of the Chilean Chemical Society, 2023)
Allelopathy is one of the alternatives used for integrated weed management (IWM), in order to minimize the use of synthetic herbicides. Allelopathy is defined as the effect produced by a chemical released by a donor plant on the development of another competitive recipient plant.Research on allelopathic interactions has been focused on agricultural crops, and allelopathic activity of indole alkaloids has been reported in cereals such as barley (Hordeum vulgare L.), whose principal natural secondary metabolite is Gramine. The degradation products of this metabolite in agricultural soils have not been investigated, however indole and derivatives substituted in aromatic ring and heterocyclic can be produced, so the role of soil in the allelopathic behavior of these compounds is not yet clear.In this work, phytotoxicity and dynamics of Gramine, indole and model series of substituted indoles in position 2 and 3 of the aromatic ring and position 5 of the aromatic ring were investigated in order to understanding the role of this metabolite in the allelopathy property of cereal barley.The phytotoxic activity against competitive cereals and weeds was determined in soil, from which the percent inhibition (% I) of seed germination and seedling growth was measured. In adsorptions study, according to the values obtained from the adsorption coefficient (Kd), it was obtained that all the series of indole alkaloids shows a moderate adsorption in Alhue soil, with the exception of indole 3-acetic acid. In the study of desorption, this compound showed a desorption percentage of 81%, according to the Kd values obtained. The persistence studies indicated a half-life (t1/2) with a range of values between 7 h and 18 days for the series of indole alkaloids studied, where the highest value of t1/2 was for indole 2-carboxylic acid and the minor one for indole 5-carbaldehyde.The dynamics of the compounds in Alhue soil affect phytotoxic activity, as well as bioavailability, so that soil plays an essential role in the phytotoxic effect of the compounds. Indole and Indole 2-carboxylic acid had the greatest phytotoxic effect, this behavior can be attributed to its greater persistence and low adsorption, that is, they are more bioavailable in Alhue soil and so the role as an allelochemical would be favorable.